2019
DOI: 10.1002/ajum.12117
|View full text |Cite
|
Sign up to set email alerts
|

Is it septic or cardiogenic shock? Papillary muscle rupture masquerading as sepsis

Abstract: Introduction: Rupture of a papillary muscle is an extremely rare but catastrophic complication of an acute myocardial infarction. Survival is time dependent on the expedition of the patient from the area of presentation to the operating theatre for surgery. Diagnosis in the ED is possible within minutes of presentation if an echo is performed by an emergency physician skilled in echocardiography, as we demonstrate. Case presentation: We present a case of a 59 years male self-presenting to the emergency departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Further supporting this, Mukherjee et al [46] emphasised the necessity of integrating echocardiography into the diagnostic repertoire of emergency physicians when reporting a case of papillary muscle rupture masquerading as sepsis. This was reinforced by both Bustam et al [47] and Frederiksen et al [48], who reported that after brief training, emergency physicians were able to accurately perform and interpret PoCE, substantially altering the course of patient care.…”
Section: Hope For Left-sided Cardiac Valve Evaluationmentioning
confidence: 97%
“…Further supporting this, Mukherjee et al [46] emphasised the necessity of integrating echocardiography into the diagnostic repertoire of emergency physicians when reporting a case of papillary muscle rupture masquerading as sepsis. This was reinforced by both Bustam et al [47] and Frederiksen et al [48], who reported that after brief training, emergency physicians were able to accurately perform and interpret PoCE, substantially altering the course of patient care.…”
Section: Hope For Left-sided Cardiac Valve Evaluationmentioning
confidence: 97%